ANALISIS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) BERBASIS LITERASI KEUANGAN DI SMA NEGERI 1 TOMOHON - Allen Ch. Manongko; Listriyanti Palangda; Mawarta Nania Marisina (Literacy: Jurnal Pendidikan Ekonomi, 2023)
ABSTRACT This study's goal is to describe in depth the BOS SMA administration at SMA Negeri 1 Tomohon in the coming year of 2022. In this article, we will discuss the following topics in order: (1) planning for SMA BOS finances in SMA Negeri 1 Tomohon; (2) implementation; (3) monitoring and evaluation; and (4) reporting. This research is a qualitative descriptive analysis. Participants in this research comprised school administrators, instructors, and students from SMA Negeri 1 Tomohon. Interviews and careful note-taking are two common data collection methods. The reliability of the data in this study was ensured by the use of triangulation and member checks. Methods for analyzing the data include data reduction, data presentation, and verification of the resulting conclusions. Based on the findings, (1) the SMA Negeri 1 Tomohon school budget team develops the RKAS with input from the School Committee, faculty, and parents of SMA students in order to allocate SMA BOS money for 2022. The RKAS was ready at the same time as the SMA BOS RAB. In 2022, there will be a two-part process for distributing SMA BOS Funds: (2) implementation, and (3) distribution. Collecting funds as the high school's BOS Treasurer. In accordance with the technical specifications laid forth in the SMA BOS 2022, schools may only utilize SMA BOS Funds to cover "non-operational" school operations. The team in charge of purchasing items and services does so effectively and efficiently. The District Education Office and the School Committee are responsible for internal evaluation and oversight. The outside implementation is the responsibility of the Provincial Education Office. The SMA BOS LPJ will be used to report on the SMA BOS Funds for both semesters of 2022. Keywords: High School BOS Funds, Planning, Implementation, Monitoring and Evaluation, Reporting ABSTRAK Tujuan penelitian ini adalah untuk mendeskripsikan secaramendalam pengelolaan BOS SMA di SMA Negeri 1 Tomohon pada tahun 2022 mendatang. Pada artikel iniakan dibahas topik-topik berikut secara berurutan: (1) perencanaan keuangan BOS SMA di SMA Negeri 1 Tomohon ; (2) implementasi; (3) pemantauan dan evaluasi; dan (4) pelaporan. Penelitian ini merupakan penelitiandeskriptif analisis kualitatif. Partisipan dalam penelitian initerdiri dari pengelola sekolah, pengajar, dan siswa SMA Negeri 1 Tomohon. Wawancara dan pencatatan yang cermat adalah dua metode pengumpulan data yang umum. Keandalan data dalam penelitian ini dipastikan denganmenggunakan triangulasi dan member check. Metodeanalisis data meliputi reduksi data, penyajian data, dan verifikasi kesimpulan yang dihasilkan. Berdasarkan temuantersebut, (1) Tim anggaran sekolah SMA Negeri 1 Tomohonmenyusun RKAS dengan masukan dari Komite Sekolah, guru, dan orang tua siswa SMA untuk mengalokasikan dana BOS SMA tahun 2022. RKAS sudah siap pada saat yang sama. waktu sebagai RAB SMA BOS. Pada tahun 2022, akan ada dua proses penyaluran Dana BOS SMA: (2) implementasi, dan (3) penyaluran. Mengumpulkan dana sebagai Bendahara BOS SMA. Sesuai dengan spesifikasiteknis yang tertuang dalam BOS SMA 2022, sekolah hanyadapat menggunakan Dana BOS SMA untuk membiayaioperasional sekolah yang “non-operasional”. Tim yang bertugas membeli barang dan jasa melakukannya denganefektif dan efisien. Dinas Pendidikan Kabupaten dan KomiteSekolah bertanggung jawab atas evaluasi dan pengawasaninternal. Pelaksanaan di luar menjadi tanggung jawab DinasPendidikan Provinsi. LPJ SMA BOS akan digunakan untukmelaporkan Dana BOS SMA untuk semester kedua tahun2022. Kata Kunci: Dana BOS SMA, Perencanaan, Pelaksanaan, Pengawasan dan Evaluasi, Pelaporan